2021
DOI: 10.1021/acsami.1c06951
|View full text |Cite
|
Sign up to set email alerts
|

A Deformable Low-Threshold Optical Limiter with Oligothiophene-Doped Liquid Crystals

Abstract: Optical limiting is a phenomenon widely recognized as the potential application for a protector of human eyes and optical sensors from irradiation with lasers. However, a high optical limiting threshold and low flexibility have restricted such applications. Here, we report that oligothiophene-doped liquid crystals (LCs) function as a low-threshold optical limiter with deformability. Irradiation of dye-doped LCs with a continuous wave (CW) laser beam brings about the formation of diffraction rings, and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Instead of the anthraquinone dyes, Zhang et al reported the usage of oligothiophene dyes to enhance the sensitivity of the LC molecular reorientation [12]. To further decrease the light intensity required for the OFT in oligothiophene-doped LCs, various approaches focusing on the incident light, alignment processing, and materials have been proposed [13][14][15][16][17][18][19]. Recently, we focused on the material design and achieved the effective molecular reorientation by doping oligothiophene dyes with ester moieties [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of the anthraquinone dyes, Zhang et al reported the usage of oligothiophene dyes to enhance the sensitivity of the LC molecular reorientation [12]. To further decrease the light intensity required for the OFT in oligothiophene-doped LCs, various approaches focusing on the incident light, alignment processing, and materials have been proposed [13][14][15][16][17][18][19]. Recently, we focused on the material design and achieved the effective molecular reorientation by doping oligothiophene dyes with ester moieties [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[12]. [13][14][15][16][17][18][19]. Recently, we focused on the material design and achieved the effective molecular reorientation by doping oligothiophene dyes with ester moieties [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Usui et al also reported an optical limiter fabricated from oligothiophene dye-doped polymer-stabilized LCs (TR5/ PSLC). [83] Because of the efficient molecular reorientation of the LCs and dichroic dyes, the optical limiter can have both a low threshold and deformability. This nonlinear reorientation induced the spatial change in the refractive index, forming diffraction rings on the screen due to self-focusing and self-phase modulation.…”
Section: Dichroic Dye-doped Lc-based Optical Limitersmentioning
confidence: 99%
“…35 The usage of PSLCs delivered optical limiters with a low threshold intensity, and the application of an electric field greatly enhanced their optical limiting threshold. 34 However, this low optical threshold intensity was only achieved by applying an electrical stimulus that can lead to a complex system. Therefore, a new NLO material that can lower the threshold intensity is necessary for developing optical switching, self-modulators, and holographic memory with simple systems.…”
Section: Introductionmentioning
confidence: 99%
“…We induced the molecular reorientation of oligothiophene dyedoped LCs at relatively low light intensities through polymer stabilization, [29][30][31] surface anchoring, 32 hybrid alignment, 33 and assistance of an electric field. 34 In polymer-stabilized LCs (PSLCs), the threshold intensity was reduced by a factor of six compared to conventional homeotropic LCs. 35 The usage of PSLCs delivered optical limiters with a low threshold intensity, and the application of an electric field greatly enhanced their optical limiting threshold.…”
Section: Introductionmentioning
confidence: 99%